Interactive open educational resources : a guide to finding, choosing, and using what's out there to transform college teaching - Shank, John D. (San Francisco, CA : Jossey-Bass, A Wiley Brand, 2014)
"Sponsored by the Association of College and Research Libraries (ACRL), this one-of-a-kind book demonstrates the best tools, resources, and techniques for discovering, selecting, and integrating interactive open educational resources (OERs) into the teaching and learning process. The author examines many of the best repositories and digital library websites for finding high quality materials, explaining in depth the best practices for effectively searching these repositories and the various methods for evaluating, selecting, and integrating the resources into the instructor's curriculum and course assignments, as well as the institution's learning management system"--
Going Further: Recommended Reading chapter 9 The Implementation Process: How to Instruct and Engage Students through ILMs; The Learning Management System and ILMs; ILM Enable Various Instructional Approaches; Synopsis; Going Further: Recommended Readings; Chapter 10 The Assessment Process: The Impact of ILMs on Student Learning; Pre-test and Post-test; Mastery Learning; The Scientific Method; Case Study: Math 110 Student Usability Testing and Calculus ILM Evaluation; Synopsis; Going Further: Recommended Readings
Includes bibliographical references (pages 163-168) and index.
Machine generated contents note: Preface: Transforming the Learning Experience through New Forms of Instructional Materials in the Digital Information Age About the Author Part 1: Interactive Learning Materials: What They Are and Why Use Them 1. Interactive Learning Materials: Engaging Learners in the Emerging Digital World 2. Defining an Emergent Class of Educational Resources: Interactive Multimedia Modules, Simulations, and Games Part 2: Finding ILMs: A Digital Exploration 3. The Discovery Process: The Art of Discovering ILMs 4. The Pioneers: Searching Online Educational Repositories in North America and the United Kingdom 5. The Educators: Searching College and University Educational Repositories 6. The Entrepreneurs: Textbook Publishers, Entertainment Media, and Educational Software Companies 7. The Exhibitors: Museums, Professional Organizations, and Governmental Organizations Part 3: Choosing and Using ILMs 8. The Selection Process: How to Choose and Evaluate ILMs 9. The Implementation Process: How to Instruct and Engage Students through ILMs 10. The Assessment Process: The Impact of ILMs on Student Learning Epilogue: How Faculty, Librarians, and Instructional Support Staff Transform Learning with ILMs in the Future References Index .
Keywords: Internet research; Electronic information resources; Internet in higher education; Open learning; EDUCATION / Higher; Electronic information resources; Internet in higher education; Internet research; Open learning